2021
DOI: 10.3390/f12111604
|View full text |Cite
|
Sign up to set email alerts
|

Growth Recovery and Phenological Responses of Juvenile Beech (Fagus sylvatica L.) Exposed to Spring Warming and Late Spring Frost

Abstract: Global change increases the risk of extreme climatic events. The impact of extreme temperature may depend on the tree species and also on the provenance. Ten provenances of Fagus sylvatica L. were grown in a common garden environment in Belgium and subjected to different temperature treatments. Half of the one year old seedlings were submitted to a high thermal stress in the spring of the first year, and all plants were exposed to a late spring frost in the second year. The high-temperature treated plants disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…Quercus showed minor losses and a fast recovery after frost treatments. Second cohort leaves emerged quickly from dormant buds which amount to c. 60% of total buds (personal observation also on adult trees), barely showing any visible impact of the frost treatments comparable to findings of other studies Vander Mijnsbrugge et al, 2021).…”
Section: Species-specific Strategies To Cope With Damaging Frost Eventssupporting
confidence: 85%
See 1 more Smart Citation
“…Quercus showed minor losses and a fast recovery after frost treatments. Second cohort leaves emerged quickly from dormant buds which amount to c. 60% of total buds (personal observation also on adult trees), barely showing any visible impact of the frost treatments comparable to findings of other studies Vander Mijnsbrugge et al, 2021).…”
Section: Species-specific Strategies To Cope With Damaging Frost Eventssupporting
confidence: 85%
“…Fagus resprouted from adventive buds and produced smaller leaves (personal observations) and a visibly reduced canopy found also by Menzel et al (2015) and Rubio‐Cuadrado, Camarero, et al (2021). Higher chlorophyll content of frozen leaves which remained longer in autumn presumably compensated for assimilation losses to some extent (Vander Mijnsbrugge et al, 2021; Zohner et al, 2019). Such stress‐related delay in senescence and compensation of assimilation losses has also been observed in beech recovering from drought (Hagedorn et al, 2016) and other studies on frost events (Zohner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are several explanations for this delayed impact on height growth. Previous research has demonstrated that the canopy recovers in 2 months from a late frost event 54 , 55 , suggesting a potential recovery through exact compensation 56 . Still, canopy recovery comes at a cost in terms of resource allocation.…”
Section: Discussionmentioning
confidence: 96%
“…At the cold distribution margin, the high plasticity in the early life-history traits may allow for increasing germination success with increasing temperatures; however, warming may negatively affect seedling establishment and survival, and thus may facilitate natural regeneration in the future only to a limited extent ( Muffler et al., 2021 ). Because of the differentiation in growth and phenological responses of beech, Vander Mijnsbrugge et al. (2021) suggested that caution should be taken when translocating provenances in anticipation of the predicted climate warming, what we can also imply grounded on the local habitat-based associations of seed and seedling properties.…”
Section: Discussionmentioning
confidence: 99%